CR-Submanifolds of Generalized f.p.k.-Space Forms. (29th April 2013) - Jaafari Matehkolaee, Mahmood
Abstract : We study sectional curvature, Ricci tensor, and scalar curvature of submanifolds of generalized f . p . k . -space forms. Then we give an upper bound for foliate ξ α -horizontal (and vertical) CR-submanifold of a generalized f . p . k . -space form and an upper bound for minimal ξ α -horizontal (and vertical) CR-submanifold of a generalized f . p . k . -space form. Finally, we give the same results for special cases of generalized f . p . k . -space forms such as S -space forms, generalized Sasakian space forms, Sasakian space forms, Kenmotsu space forms, cosymplectic space forms, and almost C ( α ) -manifolds.